Application of Particle Swarm Optimization on Reliability Sampling Inspection Program for Success or Failure Product. Issue 1 (March 2021) - Xiong, Yuanbo; Cheng, Nuo; Liu, Yunzi
Abstract: Reliability sampling inspection program for success or failure product is an intractable problem in the reliability test field. Meta-heuristic algorithm provides a new idea to solve the problem. Particle swarm algorithm is a new meta-heuristic algorithm in recent years, which has been widely used in many fields because of its simplicity but efficiency. In this paper, a reliability sampling inspection program model is developed to minimize the distance of risk. In addition, the mechanism of the particle swarm algorithm is expounded, and a case study reveals that the method in this paper is feasible and effective.